Meningkatkan Kemampuan Apresiasi Tari Traditional Dengan Model Pembelajaran Case Based Learning - Prihanita Kusuma Wardani; Ojang Cahyadi; Elindra Yetti (Jurnal Pendidikan Tari, 2023)
Traditional dance is one of the arts that must be preserved, there are values of social cultural, moral, and beauty to appreciate. Traditional dance is important to appreciate because in addition to containing beauty values, it also contains health values, moral messages, stories, and advice. Appreciation ability is very important for students to increase their desire to preserve and be proud of their culture. This study aims to improve students' appreciation for traditional dance through the application of case-based learning models. The research was a clasroom action research with the Kemmis and Mc Taggart models, using statistical quantitative and qualitative descriptive analysis. Data collection techniques through observation, interviews, tests and documentation on X IPA 6 studients at 2 Depok SHS. This study was had a second cycle of 38 students, in Cycle I and Cycle II. The results of this study were seen to increase in pre-cycle data of 69%, and increase in cycle I of 75.3 and increase in cycle II of 89.32 with satisfaction in cycle I by 50% and cycle 2 by 99%, which means that there is an improvement in the appreciation learning process Traditional dance with case-based learning models.